The experiences of non-religious children in religious education - Strhan, Anna (Journal of Religious Education, 2022)
There is growing recognition of the need for pupils to have the opportunity to engage with both religious and non-religious worldviews in religious education (RE). This recognition is bound up with issues of social justice and equality, underpinned by a desire to ensure that all young people should have the opportunity ‘to understand the worldviews of others and reflect on their own’ (Commission on Religious Education 2018: 26). In thinking about how best to provide non-religious pupils with opportunities to reflect on their own worldviews, beliefs, and moral commitments, we should take into account their current experiences in RE. This article therefore offers original insight into the experiences and perspectives of non-religious primary school children in relation to RE. We draw on data from a qualitative study exploring what it means to be ‘non-religious’ for primary school children in three different areas of England. Through presenting how these children reflect on RE, we see that they care about social justice but also that their own experiences of RE can be seen as perpetuating a ‘hermeneutic injustice’ (Fricker, 2007) as they are not being given interpretive resources to make sense of their own experiences and worldviews. We argue that giving children the opportunity to explore the kind of ‘emerging worldview’ (Beaman, 2017) that they themselves express might be one way to overcome this inequality and provide them with a language to reflect on their beliefs and values and enter into meaningful conversation with others.